The The cultural code as a factor of habitability in urban social dwelling towards sustainability - García Hernández, Alma Leticia; Mayorga Cervantes, Juan Raymundo; Ortega Ibarra, Carlos (Acta Universitaria, 2023)
In the complex system of urban social housing (VSU), eco-techniques are not used regularly, and the use of polluting energy systems is favored. By analyzing how to improve the efficient use of natural resources in the VSU, the cultural code was identified by implementing sustainable actions and eco-techniques to improve its habitability. This research was done with a mixed, exploratory, non-experimental, correlational, micro-ethnographic observation method, with a convenience and concurrence sample of 43 subjects who live in single-family homes. The results determined a significant correlation between environmental and economic efficiency in the use of eco-techniques and the meaning of their home. The cultural sense of the habitat promotes the incorporation of sustainable habits and technology, a vital point for its appropriation when valuing the use of natural resources, and it contributes to the social, environmental, and economic justice of the families under study.